Analysis of explosion pressure and residual gas characteristics of micro-nano coal dust in confined space. (March 2020) - Tan, Bo; Shao, Zhuangzhuang; Xu, Bin; Wei, Hongyi; Wang, Tian
Abstracts: In order to study the explosion characteristics of micro and nano-sized coal dust, a 20L spherical explosion test device was used to compare and analyze the explosion pressure characteristics and residual gas characteristics of five kinds of micro-nano particle dusts of 800 nm, 1200 nm, 45 μm, 60 μm and 75 μm under five concentrations (100 g/m 3 、250 g/m 3 、500 g/m 3 、750 g/m 3 、1000 g/m 3 ). The results showed that the explosion pressure characteristics were significantly related to the particle size and concentration. The time required for the nano-sized coal dust to reach the maximum explosion pressure was less than the micron. Among the five different coal dust concentrations, the best explosion concentration was 500 g/m 3, the maximum explosion pressure of 800 nm coal dust was 0.73 MPa, the maximum explosion pressure rate was 87.37 MPa s −1, and the explosion index K st was 22.35 MPa m·s −1 . The explosion hazard level of nano-sized coal dust was a strong level, while micro-sized coal dust was a weak level. Under the same coal dust concentration, the concentrations of O2, CO2 and CO after the nano-sized coal dust explosion were lower than the micro-sized. When the coal dust concentration is 500 g/m 3, the O2 and CO concentrations after 800 nm coal dust explosion are 9.3% and 503 ppm, respectively. However, the concentrations of O2 and CO after the 45 μm coal dust explosion were 10.6% and 2008 ppm. The CO/CO2 ratio after the nano-sized coal dust explosion was less than the micron. Highlights: The time required for the nano-sized coal dust to reach the maximum explosion pressure was less than the micron. The best explosive concentration of coal dust at five test concentrations was 500 g/m 3 . The explosion hazard level of nano-sized coal dust was a strong level, while micro-sized coal dust was a weak level. The concentration of residual gas after nano-coal explosion was less than the micron.